2020
DOI: 10.3233/jad-190722
|View full text |Cite
|
Sign up to set email alerts
|

Aggregates of RNA Binding Proteins and ER Chaperones Linked to Exosomes in Granulovacuolar Degeneration of the Alzheimer’s Disease Brain

Abstract: Granulovacuolar degeneration (GVD) occurs in Alzheimer's disease (AD) brain due to compromised autophagy. Endoplasmic reticulum (ER) function and RNA binding protein (RBP) homeostasis regulate autophagy. We observed that the ER chaperones Glucose -regulated protein, 78 KDa (GRP78/BiP), Sigma receptor 1 (SigR1), and Vesicle-associated membrane protein associated protein B (VAPB) were elevated in many AD patients' subicular neurons. However, those neurons which were affected by GVD showed lower chaperone levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 90 publications
(125 reference statements)
3
39
1
Order By: Relevance
“…Furthermore, a higher GVB load is found in bigenic TAPP mice that express both human tau P301L and human mutant amyloid precursor protein (APP) K670M/N671L (APP Sw ) compared to JNPL3 mice carrying only the human tau P301L transgene [54,78] (Table 2). This higher GVB frequency is likely related to the exacerbated tau pathology in TAPP mice rather than the comorbid Aβ pathology, as GVBs are absent in mouse models of pure Aβ amyloidosis by overexpression of APP Sw (Tg2576), APP Sw,Ind (J20), APP Sw/L /PS1 M146L or APP Sw /PS1 dE9 [54,67,90] although the recent detection of granular structures with an immunogenicity profile that partially overlaps with GVBs in APP Sw /PS1 dE9 mice requires further investigation [148]. Taken together, the data indicate that neither in human nor in Tg mouse brain, GVBs and extracellular Aβ pathology are associated.…”
Section: Table 2 Putative Gvb Observations In Experimental Models Andmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, a higher GVB load is found in bigenic TAPP mice that express both human tau P301L and human mutant amyloid precursor protein (APP) K670M/N671L (APP Sw ) compared to JNPL3 mice carrying only the human tau P301L transgene [54,78] (Table 2). This higher GVB frequency is likely related to the exacerbated tau pathology in TAPP mice rather than the comorbid Aβ pathology, as GVBs are absent in mouse models of pure Aβ amyloidosis by overexpression of APP Sw (Tg2576), APP Sw,Ind (J20), APP Sw/L /PS1 M146L or APP Sw /PS1 dE9 [54,67,90] although the recent detection of granular structures with an immunogenicity profile that partially overlaps with GVBs in APP Sw /PS1 dE9 mice requires further investigation [148]. Taken together, the data indicate that neither in human nor in Tg mouse brain, GVBs and extracellular Aβ pathology are associated.…”
Section: Table 2 Putative Gvb Observations In Experimental Models Andmentioning
confidence: 99%
“…A few studies have reported GVBs in tau transgenic (Tg) mouse models. GVBs are found in the brains of aged tau Tg mice expressing human mutant tau – more specifically, in mice from the strains JNPL3 [ 54 , 78 ] and pR5 [ 64 , 66 , 67 , 90 , 148 ] expressing human tau P301L (Table 2 ). In contrast, GVBs are not or only rarely found in age-matched non-Tg littermates [ 54 , 64 , 66 , 67 , 90 ].…”
Section: Gvbs As Pathological Companion Of Tau Pathologymentioning
confidence: 99%
See 3 more Smart Citations